Toddler’s Self-Regulation Strategies in a Challenge Context are Nap-Dependent - Miller, Alison L. (J Sleep Res, 2014)
Early childhood represents a time of developmental changes in both sleep and self-regulation, a construct reflecting the ability to control one’s behavior, attention, and emotion when challenged. Links between sleep and self-regulation processes have been proposed, but experimental evidence with young children is lacking. In the current study, we tested the effects of acute sleep restriction (nap deprivation) on toddlers’ self-regulation. Healthy children (n=12; 4 males; 30–36 months (33.9±1.7) slept on a strict schedule (verified with actigraphy and sleep diaries) for 5 days before each of two afternoon assessments following a Nap and a No-Nap condition (~11-day protocol). Children were videotaped while attempting an unsolvable puzzle, and 10 mutually exclusive self-regulation strategies were later coded. On average, children lost ~90 min of sleep on the No-Nap versus the Nap day. Nap deprivation resulted in moderate-to-large effects on self-regulation strategies, with decreases in skepticism (d=0.77; 7% change), negative self-appraisal (d=0.92; 5% change), and increases in physical self-soothing (d=0.68; 10% change), focus on the puzzle piece that would not fit (perseveration; d=0.50; 9% change), and insistence on completing the unsolvable puzzle (d=0.91; 10% change). Results suggest sleep serves an important role in the way toddlers respond to challenging events in their daily lives. After losing daytime sleep, toddlers were less able to effectively engage in a difficult task and reverted to less mature self-regulation strategies, than when they were well-rested. Over time, chronically missed sleep may impair young children’s self-regulation abilities, resulting in risk for social-emotional, behavioral, and school problems.